2014
DOI: 10.1016/j.cognition.2014.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Within-word serial order control: Adjacent mora exchange and serial position effects in repeated single-word production

Abstract: An essential function of language processing is serial order control. Computational models of serial ordering and empirical data suggest that plan representations for ordered output of sound are governed by principles related to similarity. Among these principles, the temporal distance and edge principles at a within-word level have not been empirically demonstrated separately from other principles. Specifically, the temporal distance principle assumes that phonemes that are in the same word and thus temporall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Thus, syllables are selectable units in Chinese, but not in English. In Japanese, Kubozono (; see also Nakayama & Saito, ) showed that morae, phonological units intermediate in granularity to syllables and phonemes and comprising one or two phonemic segments (see Kureta, Fushimi, Sakuma, & Tatsumi, and Roelofs, in this issue, for additional details concerning morae), as well as phonemes slip. This is consistent with the claim that morae are primary phonological units in Japanese (Kureta, Fushimi, Sakuma, & Tatsumi, ; Kureta, Fushimi, & Tatsumi, ).…”
Section: The Case For Proximate Unitsmentioning
confidence: 99%
“…Thus, syllables are selectable units in Chinese, but not in English. In Japanese, Kubozono (; see also Nakayama & Saito, ) showed that morae, phonological units intermediate in granularity to syllables and phonemes and comprising one or two phonemic segments (see Kureta, Fushimi, Sakuma, & Tatsumi, and Roelofs, in this issue, for additional details concerning morae), as well as phonemes slip. This is consistent with the claim that morae are primary phonological units in Japanese (Kureta, Fushimi, Sakuma, & Tatsumi, ; Kureta, Fushimi, & Tatsumi, ).…”
Section: The Case For Proximate Unitsmentioning
confidence: 99%
“…One possible explanation for the difference in effects is the difference in measurement (i.e., speech error vs. STM task performance). We nevertheless suspect that measurement is not the main cause of the difference in the effects, because accumulating evidence suggests common serial ordering mechanisms for speech production and serial order memory (e.g., Acheson & MacDonald, 2009; Nakayama & Saito, 2014). A plausible explanation may be the extent of training.…”
mentioning
confidence: 96%
“…While this error is akin to a syllable exchange, others involve a CV exchange with a nasal coda, as in /da.teN saN no ha.ra/ → da.teN sa.ra no ha.ra 'Hara with three hitting points' ( Terao, 2022 ), which cannot be a syllable error. Such cases have been attributed to the mora in Japanese ( Kubozono, 1989;Nakayama & Saito, 2014;Saito & Inoue, 2017 ), suggesting that it is a selectable unit in this language. Furthermore, parallelling the differential pattern found by Chen et al ( 2002 ) and O'Séaghdha et al ( 2010) with Mandarin syllables, form preparation experiments with Japanese participants found that initial shared onsets do not reduce latencies but initial CV sequences do ( Kureta et al, 2006 ).…”
Section: Proximate Unitsmentioning
confidence: 94%
“…ra no ha.ra ‘Hara with three hitting points’ (Terao, 2022), which cannot be a syllable error. Such cases have been attributed to the mora in Japanese (Kubozono, 1989; Nakayama & Saito, 2014; Saito & Inoue, 2017), suggesting that it is a selectable unit in this language. Furthermore, parallelling the differential pattern found by Chen et al.…”
Section: Proximate Unitsmentioning
confidence: 98%